Effects of Anonymity versus Examinee Name on a Measure of Depressive Symptoms in Adolescents - César Merino-Soto; Anthony Copez-Lonzoy; Filiberto Toledano-Toledano; Laura A. Nabors; Jorge Homero Rodrígez-Castro; Gregorio Hernández-Salinas; Miguel Ángel Núñez-Benítez (MDPI AG, 2022)
There is evidence in the literature that anonymity when investigating individual variables could increase the objectivity of the measurement of some psychosocial constructs. However, there is a significant gap in the literature on the theoretical and methodological usefulness of simultaneously assessing the same measurement instrument across two groups, with one group remaining anonymous and a second group revealing identities using names. Therefore, the aim of this study was to compare the psychometric characteristics of a measure of depressive symptoms in two groups of adolescents as a consequence of identification or anonymity at the time of answering the measuring instrument. The participants were 189 adolescents from Metropolitan Lima; classrooms were randomly assigned to the identified group (n = 89; application requesting to write one's own name) or to the anonymous group (n = 100; application under usual conditions), who responded to the Childhood Depression Inventory, short version (CDI-S). Univariate characteristics (mean, dispersion, distribution), dimensionality, reliability, and measurement invariance were analyzed. Specific results in each of the statistical and psychometric aspects evaluated indicated strong psychometric similarity. The practical and ethical implications of the present results for professional and research activity are discussed.